Burden of caregivers of patients with frontotemporal lobar degeneration – a scoping review. (15th September 2021) - Karnatz, Tina; Monsees, Jessica; Wucherer, Diana; Michalowsky, Bernhard; Zwingmann, Ina; Halek, Margareta; Hoffmann, Wolfgang; René Thyrian, Jochen
ABSTRACT: Background: Frontotemporal lobar degeneration (FTLD) is the second-most common cause of young-onset dementia. Personality and behavior changes lead to high caregiver stress and burden, but little support is available. Our aim is to present the evidence on the characteristics, challenges and unmet needs of caregivers as well as on possible interventions. Methods: We conducted a scoping review on caregiver burden using PubMed, Web of Science and ScienceDirect. A total of 69 articles were considered eligible and were analyzed in the present study. Results: Through the analysis of 69 empirical articles, our results show that caregivers of patients with FTLD are often younger in age, have children and find behavioral disturbances to be the most burdensome. Nine studies assessed the needs of and support for caregivers. Ten studies compared the burden in different forms of FTLD, 19 compared FTLD to other types of dementia, and one compared the caregiver burden between two countries. Eight studies reported on interventions for caregivers or interventions taking burden into account. One study assessed the support structure for caregivers of FTLD patients. Five case reports, eight research overviews and three reviews addressed specific needs and challenges. Conclusions: Further research should reproduce and validate efficacious interventions and focus on underage children of FTLD patients and findings from non-Western countries. Additionally, support structures for FTLD caregivers should be assessed and extended. Awareness both in the wider population and among healthcare professionals is an urgent need for the future.